Protective Effect of Prim-O-Glucosylcimifugin on Ulcerative Colitis and Its Mechanism - Yin, Yu; Liu, Kunjian; Li, Guofeng (Frontiers in Pharmacology, 2022)
Prim-O-glucosylcimifugin (POG) is an extract of Chinese traditional medicine Saposhnikov with analgesic, anti-inflammatory and antioxidant properties. The therapeutic effect of POG on dextran sulfate sodium (DSS)-induced ulcerative colitis mice models, and its underlying mechanism were further explored in this study. We found that POG significantly improved the body weight, colon length, clinical score and histological scores repaired the intestinal epithelial mucosal injury and significantly inhibited the production of relevant inflammatory factors IL-1β, IL-6 and TNF-α in vivo. 16S rDNA sequencing analysis showed that POG maintained intestinal homeostasis by regulating intestinal environmental flora. In addition, the protective effects of POG on Lipopolysaccharide (LPS) -induced RAW 264.7 cells were investigated in vitro, the activation of inflammatory AKT, NF-κBp65 and MAPK signaling pathways and the occurrence of inflammatory cytokines IL-1β, IL-6 and TNF-α were significantly inhibited by POG. In summary, POG is expected to be an effective treatment for ulcerative colitis (UC) based on its effectiveness.